Comparison of Clinical Features and Treatment Outcome in Benign and Malignant Lacrimal Sac Tumors. (31st January 2020) - Kuo, Che-Yuan; Tsai, Chieh-Chih; Kao, Shu-Ching; Hsu, Wen-Ming; Jui-Ling Liu, Catherine
Abstract : Purpose . To compare the clinical characteristics and treatment outcome between benign and malignant lacrimal sac tumors. Methods . We retrospectively reviewed the medical records of all patients with pathologically confirmed lacrimal sac lesions from 1995 to 2018 in a tertiary medical center. Results . Among 65 eligible cases, 46 (70.8%) were benign lacrimal sac tumors and 19 (29.2%) were malignant lacrimal sac tumors. Secondary malignancy from nasal or paranasal cancer accounted for 47% of malignant lacrimal sac tumors. The patient's mean age at the time of diagnosis was 60 years in the benign group and 48 years in the malignant group (p = 0.03 ). The most common presenting symptoms were a palpable lump/mass and epiphora in both groups. Palpable mass extending above the medial canthal tendon was noted in 9% of the benign group and in 74% of the malignant group, respectively (p < 0.001 ). Bloody tears were noted in 5% of the benign group and in 20% of the malignant group (p = 0.21 ). In the malignant group, 10 (52.6%) were primary tumors and 9 (47.4%) were secondary tumors. The primary sites of the metastatic tumor to the lacrimal sac area were mostly from neighboring paranasal sinuses and nasal cavity. The recurrence rate was higher in patients with malignant tumors, as compared to the benign tumors (42% and 6%, respectively, p = 0.001 ). The metastatic rate was 47% and the mortality rate was 53% in malignant lacrimal sac tumors. Conclusion . Although benign and malignant lacrimal sac tumors may present similar initial symptoms, timely diagnosis and intervention for malignant lacrimal sac lesions are important because they tend to be infiltrating tumors with a poor outcome.